Environmental Threat of Soil Erosion in the Gwang Khola Watershed, Chure Region of Nepal - Basanta Neupane; Umesh Mandal; Ayad Al-Quraishi; Mehmet Ozdemir; Raju Rai (Iraqi Geological Journal, 2023)
Chure, also known as the foothills of the Himalayas that extends from east to west of Nepal, is an essential region due to the hotspot of biological diversity and various natural resources, including recharge groundwater for the Tarai region of the country. However, the Chure region has a high rate of soil erosion due to human activities and natural processes, a severe issue in the Chure region. This study looked at soil erosion in the Gwang Khola watershed in the Chure region. We used the Revised Universal Soil Loss Equation (RUSLE) model to measure soil loss by soil erosion. The results showed that about 547,992.9 tons of soil were lost annually in the Gwang Khola watershed. The results indicated that 5,259.87 hectares of the land area were in a very low-risk zone for soil erosion. Similarly, 317.79 hectares of land had a moderate risk of soil degradation, while 13.59 hectares of forest area posed a high threat. The extreme-risk erosion area was situated above 1,250 m. In contrast, the moderate and the low-risk regions of soil erosion had a lower elevation range of 950 m to 1,250 m and 650 m to 950 m, respectively. The findings of this study may aid planners and policymakers in preventing soil erosion and protecting the ecosystem in this watershed and those with similar circumstances.